Brief assessment of cognitive function in myotonic dystrophy: Multicenter longitudinal study using computer‐assisted evaluation. Issue 5 (28th February 2022) - Deutsch, Gayle K.; Hagerman, Katharine A.; Sampson, Jacinda; Dent, Gersham; Dekdebrun, Jeanne; Parker, Dana M.; Thornton, Charles A.; Heatwole, Chad R.; Subramony, Sub H.; Mankodi, Ami K.; Ashizawa, Tetsuo; Statland, Jeffrey M.; et al.
Abstract: Introduction/Aims: Myotonic dystrophy type 1 (DM1) is known to affect cognitive function, but the best methods to assess central nervous system involvement in multicenter studies have not been determined. In this study our primary aim was to evaluate the potential of computerized cognitive tests to assess cognition in DM1. Methods: We conducted a prospective, longitudinal, observational study of 113 adults with DM1 at six sites. Psychomotor speed, attention, working memory, and executive functioning were assessed at baseline, 3 months, and 12 months using computerized cognitive tests. Results were compared with assessments of muscle function and patient reported outcomes (PROs), including the Myotonic Dystrophy Health Index (MDHI) and the 5‐dimension EuroQol (EQ‐5D‐5L) questionnaire. Results: Based on intraclass correlation coefficients, computerized cognitive tests had moderate to good reliability for psychomotor speed (0.76), attention (0.82), working memory speed (0.79), working memory accuracy (0.65), and executive functioning (0.87). Performance at baseline was lowest for working memory accuracy ( P < .0001). Executive function performance improved from baseline to 3 months ( P < .0001), without further changes over 1 year. There was a moderate correlation between poorer executive function and larger CTG repeat size (r = −0.433). There were some weak associations between PROs and cognitive performance. Discussion: Computerized tests of cognition are feasible in multicenter studies of DM1. Poor performance was exhibited in working memory, which may be a useful variable in clinical trials. Learning effects may have contributed to the improvement in executive functioning. The relationship between PROs and cognitive impairment in DM1 requires further study.